ECMO in COVID-19—prolonged therapy needed? A retrospective analysis of outcome and prognostic factors. (September 2021) - Dreier, Esther; Malfertheiner, Maximilian Valentin; Dienemann, Thomas; Fisser, Christoph; Foltan, Maik; Geismann, Florian; Graf, Bernhard; Lunz, Dirk; Maier, Lars Siegfried; Müller, Thomas; Offner, Robert; Peterhoff, David; et al.
Background: The role of venovenous extracorporeal membrane oxygenation (VV ECMO) in patients with COVID-19-induced acute respiratory distress syndrome (ARDS) still remains unclear. Our aim was to investigate the clinical course and outcome of those patients and to identify factors associated with the need for prolonged ECMO therapy. Methods: A retrospective single-center study on patients with VV ECMO for COVID-19-associated ARDS was performed. Baseline characteristics, ventilatory and ECMO parameters, and laboratory and virological results were evaluated over time. Six months follow-up was assessed. Results: Eleven of 16 patients (68.8%) survived to 6 months follow-up with four patients requiring short-term (<28 days) and seven requiring prolonged (⩾28 days) ECMO support. Lung compliance before ECMO was higher in the prolonged than in the short-term group (28.1 (28.8–32.1) ml/cmH2 O vs 18.7 (17.7–25.0) ml/cmH2 O, p = 0.030). Mechanical ventilation before ECMO was longer (19 (16–23) days vs 5 (5–9) days, p = 0.002) and SOFA score was higher (12.0 (10.5–17.0) vs 10.0 (9.0–10.0), p = 0.002) in non-survivors compared to survivors. Low viral load during the first days on ECMO tended to indicate worse outcomes. Seroconversion against SARS-CoV-2 occurred in all patients, but did not affect outcome. Conclusions: VV ECMO support for COVID-19-induced ARDS is justified if initiated early and at an experienced ECMO center. Prolonged ECMO therapy might be required in those patients. Although no relevant predictive factors for the duration of ECMO support were found, the decision to stop therapy should not be made dependent of the length of ECMO treatment.